Morphotectonic analysis of Kozani Basin (Western Macedonia, Greece) - Simou, E.; Karagkouni, V.; Papantoniou, G.; Papanikolaou, D.; Nomikou, P. (Bulletin of the Geological Society of Greece, 2013)
Kozani Basin is located in northern-central Greece and constitutes the southernmost of the Plio-Pleistocene basins of western Macedonia. Quantitative and qualitative analysis of morphological slope values, as well as the analysis of the drainage pattern in Kozani Basin confirms that the current topographic relief reflects intense neotectonic activity. Synthetic Morphotectonic Map of the under study area was carried out by means of the combined use of: (a) Digital Elevation Model (DEM), (b) Slope Distribution Map, (c) Morphological Slope Map and (d) Drainage Pattern Map. The composition of the digital modelling in conjunction with the regional geological setting, allows the identification of the main morphological discontinuities and lineaments that result from morphotectonic interpretation. The high morphological slope values indicate well-defined morphotectonic features, which mainly trend NE - SW and, secondarily, NW - SE. Distinct tectonic structures are mostly recognized in the SE margin of Kozani Basin, which is characterized by intense topographic relief. The main large-scale tectonic structure trends NE - SW and corresponds to the major Aliakmonas marginal fault zone that bounds the Kozani basin to the south. On the other hand, the NW margin’s features are indiscernible; thus, the criteria for their recognition are based on the existence of the river terraces, which reflect the tectonic control. The results of our studies are presented on the Morphotectonic Map, which is followed by our 3D model of Kozani Basin.